JARGON OF HOTEL ADVERTISEMENT IN MEDAN - Iman Hasrat Harefa; Melinawati Sarumaha; Reinjaya Sitohang (JURNAL LITTERA: FAKULTAS SASTRA DARMA AGUNG, 2020)
This article deals with the Jargon of the hotel advertisement in Medan. The data are limited to only 25 jargon. The objective of this study is to find out the forms of jargon, the most dominant forms of jargon, and the reasons for the use of jargon in the hotel advertisement in Medan. This study applies research based on descriptive qualitative. The findings of this study show that there are two forms of jargon found based on Halligan's theory. Besides, it is also found jargon in the form of a sentence. It was found that there is 25 jargon which consists of 2 occurrences for word forms (8, 00%), 9 occurrences for phrase forms (36, 00%), 14 occurrences for sentence forms (56, 00%). While the acronym and abbreviation were not found. Based on the analysis, the most dominant form of jargon used in the hotel advertisement in Medan was sentenced forms with 14 occurrences or 56, 00% for percentage. The reason for the use of jargon in the hotel advertisement in Medan is to convey information appropriately to the reader or in this case the customer with the aim of the jargon being conveyed clearly and unambiguously.